EVALUASI KEBIJAKAN PNPM MANDIRI PERDESAAN DI KECAMATAN ESSANG KABUPATEN KEPULAUAN TALAUD - Matandatu, Maslin; Dengo, Salmin; Plangiten, Novva (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT: The purpose of this study was to evaluate the results and impact of policy PNPM Rural inDistrict Essang Talaud Islands. The method used is descriptive qualitative method. Informants were takenfrom PNPM Rural actors at the district level, the PNPM Rural actors at the village level, and the citizensPokmas members in several villages. Informants who were interviewed as many as 10 people. Datacollection techniques used were interviews. Data was analyzed using qualitative descriptive analysistechniques-interactive model of Miles and Hubernann.Based on research results ditariki conclusions: (1) The results of PNPM Rural in DistrictEssang generally pretty good views of some aspects such as: the allocation and disbursement of funds,the management / implementation activities and the realization of the activities. (2) PNPM Rural inDistrict Essang impact on poverty reduction seen from several aspects such as: pencipaan / increaseempowerment of the economy of the poor, creation / enhancement of independence of the poor, realize orimprove the quantity and quality of facilities prasanara basic social and economic community, increasethe participation of the various parties in efforts to reduce poverty, and increase the welfare of society orof poor households.Based on the results of this penellian then it can be recommended some suggestions asfollows: (1) the PNPM Rural Policy would that be continued by the present government's. (2) The resultsof PNPM Mandiri in Rural Areas that have been created / materialized during cerned shall continue to bemaintained and preserved to improve social welfare / poor households.Keywords: Results and Impact of Policy, PNPM Mandiri.